Varicose vein disease in children with klippel-trenaunay syndrome - Yu.O. Syniachenko (Zdorovʹe Rebenka, 2017)
The article presents a review of the literature, which describes the clinical picture and diagnosis of varicose vein disease in Klippel-Trenaunay syndrome, methods of treatment with intravenous and transcutaneous laser coagulation, endovenous radioablation, foam sclerotherapy of vessels and venectomy. There are underlined genetic defects in the genesis of the disease, the role of pro-inflammatory and immunoregulatory imbalance of cytokines, growth factors, cell adhesion molecules, matrix metalloproteinases etс. in pathogenic constructions of venous damage. This congenital vascular pathology is not as rare as it is commonly thought, and the patients suffering from this pathology since childhood are often being unsuccessfully treated in adulthood for varicose veins, elephantiasis and recurrent phlebothrombosis, when diagnosis of Klippel-Trenaunay syndrome have never previously established. This literature review has to attract the attention to the problem under discussion not only of pediatricians, but also of therapeutists and vascular surgeons-phlebologists.